AZAS PROPORSIONALITAS SEBAGAI PERWUJUDAN DOKTRIN KEADILAN BERKONTRAK - Agus Yudha Hernoko (Perspektif, 2007)
The objective of this article is to argue that the issue of equal and unequal position of the parties is irrelevant to commercial contract. The essence of commercial contract that ponders business relationship without interruption does not deal with the issue of mathematical equality; rather it emphasizes on proportional exchange of interests of the parties irrespective of result obtained by the parties. There are three important things in this paper found. First, the principle of proportionality is applied in the entire phases of contract, i.e. in negotiation, formation, and enforcement phases. Second, the principle of proportionality is not perceived from mathematical equality perspective but it is viewed from fair exchange process and proportionate result, which is acceptable by both parties. Third, the principle of proportionality is a doctrine of "fair contract", which improves the doctrine of freedom of contract that may lead to unfairness. It is recommended in this dissertation that jurists, currently be not regard the doctrine of freedom of contract sacred; rather they shall find other philosophical basis to develop "fair contract" procedurally as well as substantively.